Developing a Thematic English Module for Elementary School Students Using the 4D Model - Husnaini; Alifa Zahra Fadhilah (Universitas Islam Negeri Palopo, 2025)
This research aimed to develop a thematic English module as supplementary learning material for sixth-grade students at SD Muhammadiyah 1 Palopo. The study was conducted in response to the limited availability of standardized English teaching materials at the elementary level and the need for contextual resources that match young learners' characteristics. This research employed the Research and Development method using the 4D model, consisting of define, design, develop, and disseminate. Data were collected through a teacher interview, students' needs-analysis questionnaire, expert validation sheets, and limited dissemination responses. The participants involved 28 sixth-grade students and one English teacher. The needs analysis was based on Hutchinson and Waters' framework covering necessities, lacks, wants, and learning needs. The findings showed that students needed vocabulary support, sentence examples, speaking practice, and engaging learning activities, while their main difficulties involved sentence construction, vocabulary comprehension, and pronunciation. Based on these needs, the module was designed with three thematic topics and several features, including learning objectives, motivational quotes, magic words, QR-code listening activities, chatter corner, story time, creative writing, a self-reflection journal, and lesson plans. The product was validated by content, language, and design-layout experts and obtained an average score of 87.3%, categorized as good, valid, and applicable with minor revisions. The dissemination with students and the teacher showed positive responses because the module was attractive, easy to use, and relevant to classroom needs. The module is expected to support teachers in delivering English lessons and help elementary students learn English through integrated, interactive, and meaningful activities.